Atypical CT Findings and Clinical Correlation Of COVID-19 Pneumonia - Gülcan GÜCER ŞAHİN; Tuğba İlkem KURTOĞLU ÖZÇAĞLAYAN; Ayhan ŞAHİN; Ömer ÖZÇAĞLAYAN; Hadi SASANİ (Namık Kemal Tıp Dergisi, 2020)

(untitled)
Aim: Our study aimed to evaluate the atypical CT findings and concomitant pathologies of COVID-19 pneumonia and clinical and laboratory findings and compare them with typical CT findings.Materials and Methods: A total of 69 patients were diagnosed with COVID-19, 14 of which were atypical (20.2%), and 55 of which were typical (79%) chest computed tomography (CT) findings. CT images and clinical and laboratory data of patients with atypical findings were retrospectively analyzed. Lesions of the typical and atypical group and CT severity scores were compared.Results: Atypical CT findings were centrilobular nodule, tree in bud, pleural effusion, lobar/segmental consolidation, bronchiectasis, pulmonary embolism, and mosaic attenuation by typical lesions with ground-glass opacity with/without consolidation. CT severity score was significantly higher in the atypical group (p <0.001). CRP, procalcitonin, the neutrophil rate increased, and the lymphocyte count decreased in patients with a high CT severity score. Comorbidity was common in the atypical group (50%).Conclusion: High CT severity score and widespread lung involvement of the patient group with atypical CT findings may be due to disease progression or other concomitant diseases. Atypical lesions accompanying typical lesions may cause false negativity in reporting. As radiologists' experience with COVID-19 pneumonia increases, it may improve that they categorize these images as typical or atypical.